MODEL OF STUDENTS’WORKBOOK BASED ON DAYAK LOCAL WISDOM FOR SMPN 4 AIR BESAR - Musuwani, Musuwani; Sutapa, Y. Gatot; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was to develop model of students’ workbook for junior high school based on Dayak’s local wisdom. The research participants were 24 students of second grade of SMPN 4 Air Besar. Designed through the implementation of ADDIE (Branch and Gagne 2009), the collected data revealed that the students were more interested in learning English. They looked happy to use the products. In the contextual analysis result and its validation, the materials development experts also recomend strongly that these products are more relevant to the needs of rural area students especially the dayak ones. With some feedbacks from the implementation, it was found that the students were much more active and creative in the learning process. Thus, this product is deserved to use as an alternative material for English subject at junior high school of rural areas.Keywords: local wisdom, modelof student’s workbook, materia development,rural area